2014
DOI: 10.1186/1471-2474-15-59
|View full text |Cite
|
Sign up to set email alerts
|

Tactile acuity training for patients with chronic low back pain: a pilot randomised controlled trial

Abstract: BackgroundChronic pain can disrupt the cortical representation of a painful body part. This disruption may play a role in maintaining the individual’s pain. Tactile acuity training has been used to normalise cortical representation and reduce pain in certain pain conditions. However, there is little evidence for the effectiveness of this intervention for chronic low back pain (CLBP). The primary aim of this study was to inform the development of a fully powered randomised controlled trial (RCT) by providing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 24 publications
0
32
0
8
Order By: Relevance
“…Five full-texts were not found and 96 were excluded with reasons (see the Supplementary Table S7). Ten additional studies (Grod and Diakow, 2002;Barker et al, 2008;Wand et al, 2010Wand et al, , 2011Preston and Newport, 2011;Nishigami et al, 2012;Diers et al, 2013;Ryan et al, 2014;Treleaven and Takasaki, 2015;Beales et al, 2016) were identified and considered eligible by searching the reference lists of included papers and reviews considered of interest for the aim of this work. Thirty-seven studies, analysing an overall sample of 1291 patients (1,094 in evaluation studies, and 197 for interventions ones), were included in the qualitative analysis and the end of the selection process (see the Figure 2 for a flowchart of the entire process).…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Five full-texts were not found and 96 were excluded with reasons (see the Supplementary Table S7). Ten additional studies (Grod and Diakow, 2002;Barker et al, 2008;Wand et al, 2010Wand et al, , 2011Preston and Newport, 2011;Nishigami et al, 2012;Diers et al, 2013;Ryan et al, 2014;Treleaven and Takasaki, 2015;Beales et al, 2016) were identified and considered eligible by searching the reference lists of included papers and reviews considered of interest for the aim of this work. Thirty-seven studies, analysing an overall sample of 1291 patients (1,094 in evaluation studies, and 197 for interventions ones), were included in the qualitative analysis and the end of the selection process (see the Figure 2 for a flowchart of the entire process).…”
Section: Study Selectionmentioning
confidence: 99%
“…A graphical distribution of included studies grouped by clinical conditions examined is shown in Figure 3. Twenty-five studies (Grod and Diakow, 2002;Moseley, 2008;Wand et al, 2010Wand et al, , 2013bWand et al, , 2014Wand et al, , 2016Docherty et al, 2012;Lauche et al, 2012a;Valenzuela-Moguillansky, 2013;Hirakawa et al, 2014;Gilpin et al, 2015;Mibu et al, 2015;Nishigami et al, 2015Nishigami et al, , 2017Nishigami et al, , 2018Treleaven and Takasaki, 2015;Beales et al, 2016;Janssens et al, 2017;Moreira et al, 2017;Adamczyk et al, 2018a,b;Ehrenbrusthoff et al, 2018;Magni et al, 2018;Martínez et al, 2018) studies concerned the assessment of SoP dysfunctions, while twelve interventional studies (Barker et al, 2008;Preston and Newport, 2011;Wand et al, 2011Wand et al, , 2013aMorone et al, 2012;Paolucci et al, 2012;Diers et al, 2013;Vetrano et al, 2013;Ryan et al, 2014;Louw et al, 2017;Stanton et al, 2018;Nishigami et al, 2019) investigated the effects of perception-based intervention to reduce pain or to correct perceptual distortions. One study, (Lauche et al, 2012a) was included both in assessment and in intervention studies: it is a qualitative study i...…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations